2018
DOI: 10.1021/acs.molpharmaceut.8b00499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Linker Modification on Tumor-to-Kidney Contrast of 68Ga-Labeled PSMA-Targeted Imaging Probes

Abstract: Ga-PSMA-11 is currently the most popular prostate-specific membrane antigen (PSMA) radioligand used in the clinic to detect prostate cancer and metastases. However, the high uptake of Ga-PSMA-11 in kidneys can create halo-artifacts resulting in lower detection sensitivity for lesions adjacent to the kidneys. In this study, we developed twoGa-labeled PSMA-targeted tracers, Ga-HTK01166 andGa-HTK01167, based on Ga-PSMA-617 with the goal of improving tumor-to-kidney ratio compared toGa-PSMA-11. The 2-naphthylalani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 49 publications
0
57
1
Order By: Relevance
“…The low LogD value of [ 99m Tc]Tc-15 compared to [ 99m Tc]Tc-16 suggests that it is more hydrophilic. However, the presence of two phenyl amino acid groups in the spacer did not show much influence on the LogD value compared to other reports, likely because the phenyl amino groups are hindered inside the trivalent complex [4,54].…”
Section: Discussioncontrasting
confidence: 79%
“…The low LogD value of [ 99m Tc]Tc-15 compared to [ 99m Tc]Tc-16 suggests that it is more hydrophilic. However, the presence of two phenyl amino acid groups in the spacer did not show much influence on the LogD value compared to other reports, likely because the phenyl amino groups are hindered inside the trivalent complex [4,54].…”
Section: Discussioncontrasting
confidence: 79%
“…Previous studies have demonstrated that there is PSMA expression in normal kidney proximal tubular epithelial cells . Hence, radiation toxicity to kidneys due to the fast clearance of radioligands through the urinary tract is of concern for their application for RLT . However, neither acute nor long‐term kidney toxicity has recently been reported to be a clinical problem in patients treated with [ 177 Lu]Lu‐PSMA‐617 .…”
Section: Discussionmentioning
confidence: 99%
“…50 Hence, radiation toxicity to kidneys due to the fast clearance of radioligands through the urinary tract is of concern for their application for RLT. 6,51 However, neither acute nor long-term kidney toxicity has recently been reported to be a clinical problem in patients treated with [ 177 Lu]Lu-PSMA-617. 51 It is noteworthy that human kidneys have lower PSMA expression than mouse kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations